2016
DOI: 10.1186/s12889-016-3871-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a participatory organizational-level occupational health intervention on job satisfaction, exhaustion and sleep disturbances: results of a cluster randomized controlled trial

Abstract: BackgroundWe examined whether the implementation of a participatory organizational-level intervention aiming to improve the working environment with a focus on the core task at work, increased job satisfaction and reduced exhaustion and sleep disturbances among pre-school employees.MethodsThe study sample consisted of 41 intervention group pre-schools with 423 employees and 30 control group pre-schools with 241 employees. The intervention lasted 25 months and consisted of seminars, workshops, and workplace spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
2
15
0
1
Order By: Relevance
“…Experience has shown that the screening of sleeping disorders and intervention to determine poor sleep quality can be incorporated into current health surveillance activities without a significant increase in medical costs or lost of medical time, and result in a substantial improvement in the quality of health care [ 94 , 130 ]. A number of health promotion programs targeted at sleepiness and fatigue prevention have been implemented [ 131 , 132 , 133 , 134 , 135 ] and proved to be effective; other programs, however, have had negative results [ 136 , 137 ]. In many studies both the internal and external validity of findings have been limited and the range of factors investigated has been insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Experience has shown that the screening of sleeping disorders and intervention to determine poor sleep quality can be incorporated into current health surveillance activities without a significant increase in medical costs or lost of medical time, and result in a substantial improvement in the quality of health care [ 94 , 130 ]. A number of health promotion programs targeted at sleepiness and fatigue prevention have been implemented [ 131 , 132 , 133 , 134 , 135 ] and proved to be effective; other programs, however, have had negative results [ 136 , 137 ]. In many studies both the internal and external validity of findings have been limited and the range of factors investigated has been insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…The original aim of this trial was to study whether the intervention had an impact on employees’ well-being and sickness absence. Results on these primary endpoints are published elsewhere [10, 11]. Change in WSC was not a defined endpoint of the trial.…”
Section: Introductionmentioning
confidence: 99%
“…As illegitimate tasks have been shown to act as a job stressor it is important to investigate how they affect physicians’ health and well-being [ 4 , 7 , 20 ]. Previous research has shown that illegitimate tasks are negatively related to job satisfaction [ 4 , 6 ] and positively related to counterproductive behaviour [ 2 ] and stress reactions among employees [ 21 ].…”
Section: Introductionmentioning
confidence: 99%